EFEKTIVITAS KINERJA KEPALA SEKOLAH DALAM MEMBERDAYAKAN GURU UNTUK MENINGKATKAN PRESTASI KERJA GURU DI MAS NURUL IMAN SUKARAMAI KECAMATAN BILAH BARAT KABUPATEN LABUHANBATU - Nurafni Siregar (Hijri, 2018)
This study aims to find out the principal's technique in empowering teachers toimprove teacher work performance, knowing the stages of effective teacher empowerment conducted by the principal to improve teacher work performance, knowing the principal program in effective teacher empowerment, knowing the existing barriers in the empowerment of teachers, find out how the principal perform assessment of teacher work performance through empowerment of teachers work. This study used qualitative research methods. The data collection of this research is done by using observation, interview, and documentation study. and the subject of research are: principals and teachers. The findings of this research are 1) Stages of teacher empowerment conducted by the Head of the school at MAS Nurul Iman Sukaramai is (a) to prepare everything needed in the empowerment of teachers including the facilities and infrastructure. (b) make teachers confident, and (c) provide guidance and direction to teachers, 2) The techniques of the principal in teacher empowerment at MAS Nurul Iman Sukaramai are (a) strategies to include teachers for training, (b) cooperation between principal and teacher, and (c) direct communication with the teacher (sharing with teachers), 3) Principal work principal conducted at MAS Nurul Iman Sukaramai is training for each subject teacher such as BIMTEK, K13 training and meeting which is held once a month, and the program is tailored to the vision of the school's mission, 4) The common barrier in teacher empowerment is the absence of some teachers in the implementation of the teacher empowerment program that is training due to the reason of each teacher 5) in assessing the achievement teacher work seen from how the success of his students, if a student is successful or achievement means that the teacher is able to make the child idiknya suskes in learning is because the teacher. It can be concluded that the effectiveness of Principal Performance in Empowering Teachers to Improve Teacher Work Achievement in MAS Nurul Iman Sukaramai District West Bilah Labuhanbatu District, then I can draw the conclusion that is good enough to run well the principal's performance in empowering teachers and also teacher work performance increased.Keywords:   Principal   Performance,   Empowering   Teachers,   Teacher   Work Achievement.